The Relationship between Psychological Stress with Breastfeeding Frequency and Breastmilk Volume during the COVID-19 Pandemic - Murdhiono, Wahyu Rochdiat; Okinarum, Giya Yulilania (Jurnal Keperawatan Soedirman, 2022)
Breastfeeding mothers have limited access to healthcare facilities during the pandemic, thus raising their risk of psychological stress. This study aimed to analyze the correlation between psychological stress with breastfeeding frequency and breastmilk volume. A cross-sectional survey was conducted with 120 exclusively breastfeeding mothers. The Perceived Stress Scale (PSS) was employed as a stress assessment indicator measuring tool. The measurement of breastmilk volume was performed using a manual breast pump two hours before or after the baby suckles to restore milk production. The frequency of breastfeeding was calculated by adding up the number of times the baby is breastfed in a day. The chi-square test was used in this study. It was found that 68 respondents (56.7%) reported experiencing mild to moderate stress. Stress levels were found to have a significant connection with breastfeeding frequency and breastmilk volume (p < 0.05). The respondents who experienced severe stress have a 2.63-times higher risk for breastfeeding <8 times/day and 33.2 times higher risk of producing breast milk <100cc than respondents who experienced mild-moderate stress. Concerns about the psychological stress of breastfeeding mothers highlight the critical need for good mental health and broader help from families during the pandemic.